Proof: Get Begin Expr Parent 67
Let's prove the following theorem:
if the following are true:
- expression state at time 67 = "begin_expr"
- the expression at time 67 =
joe.jump()
- parent stack at time 67 = [ ]
then parent stack at time 68 = [ joe.jump()
, [ ] ]
Proof:
Given
1 | expression state at time 67 = "begin_expr" |
---|---|
2 | the expression at time 67 = joe.jump() |
3 | parent stack at time 67 = [ ] |
# | Claim | Reason |
---|---|---|
1 | parent stack at time (67 + 1) = [ joe.jump() , parent stack at time 67 ] |
if expression state at time 67 = "begin_expr" and the expression at time 67 = joe.jump() , then parent stack at time (67 + 1) = [ joe.jump() , parent stack at time 67 ] |
2 | [ joe.jump() , parent stack at time 67 ] = [ joe.jump() , [ ] ] |
if parent stack at time 67 = [ ], then [ joe.jump() , parent stack at time 67 ] = [ joe.jump() , [ ] ] |
3 | parent stack at time (67 + 1) = [ joe.jump() , [ ] ] |
if parent stack at time (67 + 1) = [ joe.jump() , parent stack at time 67 ] and [ joe.jump() , parent stack at time 67 ] = [ joe.jump() , [ ] ], then parent stack at time (67 + 1) = [ joe.jump() , [ ] ] |
4 | 67 + 1 = 68 | 67 + 1 = 68 |
5 | parent stack at time (67 + 1) = parent stack at time 68 | if 67 + 1 = 68, then parent stack at time (67 + 1) = parent stack at time 68 |
6 | parent stack at time 68 = [ joe.jump() , [ ] ] |
if parent stack at time (67 + 1) = parent stack at time 68 and parent stack at time (67 + 1) = [ joe.jump() , [ ] ], then parent stack at time 68 = [ joe.jump() , [ ] ] |
Comments
Please log in to add comments